Polarization independent silicon micro antenna based on a subwavelength metamaterial - Sarra Salhi; Xiaochen Xin; Daniel Benedikovič; Carlos Alonso-Ramos; Laurent Vivien; Delphine Marris-Morini; Eric Cassan; Winnie N. Ye; Daniele Melati (Scientific Reports)
Abstract Optical antennas are key components of an optical phased array system, enabling light coupling between the chip and the free space. In such systems, surface gratings are commonly used as antenna elements, which however suffer from a strong polarization sensitivity of their scattering angle and efficiency. Here, we propose a versatile approach to realize micro antennas based on surface gratings with a polarization insensitive behavior exploiting a subwavelength metamaterial in the silicon-on-insulator platform. In the experimental demonstration, the antenna successfully achieves the same diffraction angle of 10° for both TE and TM polarizations and an estimated scattering efficiency of -4 dB despite a very compact footprint of 6.4 $$μ m$$ x 2.9 $$μ m$$ . The difference in diffraction efficiency between the two polarizations remains smaller than 1 dB over a bandwidth of 31 nm.